EIB Working Paper 2023/03 - The effect of EIB operations on private sector lending outside the European Union - EUROPEAN INVESTMENT BANK (European Investment Bank, 2023)
Does an increase in lending by multinational development banks affect the private lending activity in developing countries? This paper shows that this is indeed the case using data on loans and investments by the EIB in combination with data on syndicated loans. We find that a pronounced increase in EIB operations is followed by a surge in the number and volumes of syndicate loans in countries outside the European Union. Our results suggest that multinational banks can incentivise private sector lending by playing an important role in signalling to private markets that borrowers in emerging and developing countries are safe.